1997
DOI: 10.2337/diacare.20.6.971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laboratory Test Frequency and Test Results Between African-Americans and Caucasians With Diabetes: Opportunity for Improvement: Findings from a large urban health maintenance organization

Abstract: The opportunity exists to improve the process of care for both African-Americans and Caucasians with diabetes in an HMO setting. The need to improve glycosylated hemoglobin results and subsequently limit complications is especially pressing among the African-American population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 19 publications
1
41
1
Order By: Relevance
“…In particular, the combined race and sex effect found in our study may reflect differences in the availability of social support and its relationship to selfmanagement (42,43). Other researchers have found evidence of a combined race and sex effect in quality and outcomes (7,10,28,44,45).…”
Section: Race and Long-term Diabetes Managementmentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, the combined race and sex effect found in our study may reflect differences in the availability of social support and its relationship to selfmanagement (42,43). Other researchers have found evidence of a combined race and sex effect in quality and outcomes (7,10,28,44,45).…”
Section: Race and Long-term Diabetes Managementmentioning
confidence: 95%
“…A high prevalence of poor glycemic control and outcomes among black diabetic patients (7)(8)(9)(10)(11)(12)(13)(14) may be attributable in part to inequalities in insurance coverage (15,16) and lower quality of care within clinics serving predominantly black patients (17)(18)(19). Yet, racial differences in care have also been demonstrated within coordinated care systems, such as the Veterans Administration health system (20 -23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (14,15,50 -55) have investigated quality of care and intermediate outcomes of care. Unfortunately, with the exception of four studies (14, 53,55,56), most research has treated the measurements separately and not analyzed the associations. The first study (53) examined several factors that may explain why black patients, compared with whites, have worse intermediate outcomes (glycemic control).…”
Section: Ethnic Differences In Quality Of Carementioning
confidence: 99%
“…However, in this study, no ethnic differences in glycemic control were found. In the second study (55), process of care (frequencies of tests: e.g., A1C) of African Americans and Caucasians were compared. The finding that African Americans were in poorer metabolic control than Caucasians led to the analysis of the relationship of glycemic control to determine test frequency per group.…”
Section: Ethnic Differences In Quality Of Carementioning
confidence: 99%